Effectiveness of three insecticides against mustard aphid and predator under field condition - Maula, AKMM; Shah, MMR; Siddquie, NA; Mamun, MAA; Begum, M (Bangladesh Journal of Agricultural Research, 2010)
Studies were conducted in the field to determine the effectiveness of three insectidicdes, Metasystox-R 25EC, Dimethion 40 EC, and Fentro 50 EC applied against mustard aphid, Lipaphis erysimi Kalt. and measure their toxic action on the predator Coccinella septempunctata L. The mustard plants were sprayed with the insecticides at 0.05% and 0.025% a. i. at 50 and 70 days after sowing. The mortality of both mustard aphid and the predator was assessed at 1, 4, and 7 days after first and second spraying of insecticides. Metasystox-R showed the most effectiveness among the three insecticides causing the highest mortality of mustard aphid followed by Dimethion and Fentro. But the lowest mortality of Coccinella septempunctata was obtained in Dimethion treated plot, and Fentro treated plot showed the highest mortality indicating that the Dimethion was less toxic and Fentro was more toxic to the predator. Keywords: Effectiveness; insecticides; mustard aphid; predator. DOI: 10.3329/bjar.v35i1.5880 Bangladesh J. Agril. Res. 35(1) : 179-187, March 2010